Analisis Yuridis dan Implikasi Penegakan Hukum dalam Menangani Perdagangan Organ Tubuh Manusia - Wulandari, Choirunisa Tri; Agustin, Nindi; Cahyaning Rizky, Salsabilla; Abdillah, Melani Fajri; Astuti, Mia Septiananda (Lentera Ilmu, 2024)
Generally, this illegal activity is called human organ trafficking because the parts of human organs are exchanged and money is obtained after some time. Trafficking in human bodies is also a serious problem because it does not meet useful standards and has many negative effects. In 1987, the World Health Organization (WHO) first banned the trade in human organs, and about 5 percent of global organ transplants are part of the illegal operation, a concerted fight against WHO guidelines. Of all the organs in the body, the kidneys are in the most demand because 10 percent of the world's population has chronic kidney failure. The purpose of writing this article is to analyze and learn more about the buying and selling of organs, which almost leads to human trafficking. This article focuses on a statutory review of organ procurement and supply violations, legal challenges to the requirements of the Organ Procurement and Supply Act, and recommendations for government enforcement and government action to manage it. procurement and delivery of organs. The research strategy used in this article can be a subjective approach using a library research strategy. At the time of writing, it appeared that trading in human organs is strictly prohibited by law in Indonesia. This prohibition is based on the Criminal Code and the Social Code. Because this activity is abuse because it replaces human organs. Section 345 of Act No. 1 of 2023 contains one of the few measures that the government uses to address this challenge. Keywords: Buying/selling Human Organs;Criminal Offense; WHO